2023
DOI: 10.3389/fnut.2023.1155436
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of high-fat diet with n-3 PUFAs enhanced beef tallow attenuates dyslipidemia and endoplasmic reticulum stress in tunicamycin-injected rats

Abstract: IntroductionMetabolic syndrome (MetS) is considered as a complex, intertwined multiple risk factors that directly increase the risk of various metabolic diseases, especially cardiovascular atherosclerotic diseases and diabetes mellitus type 2. While lifestyle changes, including dietary intervention are effective in mitigating or preventing MetS, there are no specific therapies against MetS. Typical western diets comprise of high saturated fatty acid, cholesterol, and simple sugar; consequently their consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…MUFA and PUFA: Studies have found that MUFA can mitigate inflammation by modulating the production of inflammatory mediators and regulating neutrophil infiltration [ 41 ]. Potential underlying mechanisms include the reduction of endoplasmic reticulum stress [ 42 ], enhancement of vascular endothelial inflammation, and systemic inflammatory responses [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…MUFA and PUFA: Studies have found that MUFA can mitigate inflammation by modulating the production of inflammatory mediators and regulating neutrophil infiltration [ 41 ]. Potential underlying mechanisms include the reduction of endoplasmic reticulum stress [ 42 ], enhancement of vascular endothelial inflammation, and systemic inflammatory responses [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood was collected via cardiac puncture, allowed to clot at room temperature for 30 min, and then centrifuged (LaboGene, Lynge, Denmark) at 1000× g at 4 • C for 15 min to separate the serum [29]. Liver and WATs, including epididymal adipose tissue (EAT), retroperitoneal adipose tissue (RAT), mesenteric adipose tissue (MAT), and perirenal adipose tissue (PAT), were collected and weighed [30]. Feces were collected from the cecum and transferred to 1.5-mL centrifuge tubes (SPL Life Sciences, Pocheon, Republic of Korea).…”
Section: Mice Experiments and Dietsmentioning
confidence: 99%